Identifikasi Unsur Hara Makro Primer pada Daerah Pengembangan Tanaman Sorgum (Shorgum bicolar L.) di Desa Patawang, Kecamatan Umalulu, Kabupaten Sumba Timur - Ndamunamu, Irvan Njoni; Killa, Yonce Melyanus; Kapoe, Suryani K.K.L. (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The availability of nutrients in the soil, whether in low, medium, or high conditions, is very vital. Knowing the chemical properties of the soil such as nitrogen, potassium, phosphorus is important because this is the basis for determining the type and dosage of the right fertilizer for sorghum plants. This study aims to identify primary soil macronutrients in the sorghum cultivation area in Patawang Village, Umalulu District, East Sumba Regency. The study was conducted from April to June 2024. The method used was a survey with a descriptive quantitative approach, using a purposive sampling method in the Sorghum development area. Soil samples were taken based on the position and area of the land, then analyzed in the laboratory for chemical properties such as N, P, K, and soil pH. The results of soil analysis from soil samples showed that the content of N nutrients ranged from 0.12-0.48% (low to moderate status), P ranged from 23.97-99.04 pmm (low to very high status), K ranged from 0.36-0.92 me/100g (moderate to very high status), and soil pH ranged from 6.90-7.97 H2O (neutral to slightly alkaline status). Based on the results of the analysis, it can be seen that the Nitrogen element is lacking in the soil. Based on this study, it is recommended to consider adding Nitrogen, Phosphorus, and Potassium fertilizers through plant residues and animal waste, as well as using chemical fertilizers with appropriate doses to support the agriculture of the farming community in Patawang Village, Umalulu District.